Unitary Operator Bases and Q-deformed Algebras - Galetti, D. [UNESP]; Pimentel, B. M. [UNESP]; Lima, C. L.; Lunardi, J. T. (My University, 1998)
Starting from the Schwinger unitary operator bases formalism constructed out of a finite dimensional state space, the well-known q-deformed commutation relation is shown to emerge in a natural way, when the deformation parameter is a root of unity.
Keywords: Finite-dimensional spaces; Q-algebras; Schwinger operator bases